2008
DOI: 10.1016/j.cbpb.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of lutein and zeaxanthin in rhesus monkeys: Identification of (3R,6′R)- and (3R,6′S)-3′-dehydro-lutein as common metabolites and comparison to humans

Abstract: Lutein and zeaxanthin are xanthophylls that can be found highly concentrated in the macula of the retina. They are thought to protect the macula through their role as blue-light filters and because of their antioxidant and singlet oxygen quenching properties. Examination of metabolites unique to lutein and zeaxanthin such as 3′-dehydro-lutein, and of their stereochemistry may provide insight to the mechanism by which they are formed and by which they exert protection. To evaluate the formation of such metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…This assumption is supported by the previous report that the plasma level of 3-hydroxy-␤ , -caroten-3 ′ -one was increased in humans and rhesus monkeys fed lutein ( 37,38 ). However, the oxidative activity of the ␤ -end group in zeaxanthin is suggested to be higher than that of the -end group in lutein, because the formation rate constant of 3-hydroxy-␤ , -caroten-3 ′ -one from zeaxanthin was found to be higher than that from lutein in Cohn and colleagues' kinetic study of lutein and zeaxanthin orally administered to human subjects ( 36,38 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This assumption is supported by the previous report that the plasma level of 3-hydroxy-␤ , -caroten-3 ′ -one was increased in humans and rhesus monkeys fed lutein ( 37,38 ). However, the oxidative activity of the ␤ -end group in zeaxanthin is suggested to be higher than that of the -end group in lutein, because the formation rate constant of 3-hydroxy-␤ , -caroten-3 ′ -one from zeaxanthin was found to be higher than that from lutein in Cohn and colleagues' kinetic study of lutein and zeaxanthin orally administered to human subjects ( 36,38 ).…”
Section: Discussionsupporting
confidence: 79%
“…Based on the metabolic activity of postmitochondrial fraction of mouse liver observed in the present study, we speculate in the plasma of humans and rhesus monkeys fed zeaxanthin ( 36,37 ). In particular, the presence of equal amounts of two diastereomers (3 R ,6 ′ R and 3 R ,6 ′ S ) of 3-hydroxy-␤ , -caroten-3 ′ -one in the plasma of rhesus monkeys was quite consistent with the oxidation of a ␤ -end group proposed in the present study.…”
Section: Discussionsupporting
confidence: 61%
“…In particular, this is one of the few studies that have detected dehydrolutein, an oxidized form of lutein and zeaxanthin (Gesa et al 2008), in the integument of birds (Costantini et al 2009). Interestingly, the eye ring contains very high amounts of carotenoid esters.…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that lutein and zeaxanthin are transported into retina in the same ratio as in plasma, and then transferred to macula where lutein is preferentially converted into meso -zeaxanthin [47,48,49,50,51]. These observations strongly suggest the importance of lutein, zeaxanthin and meso -zeaxanthin in the management of good eye health [51,52,53]. Several studies have shown that incidences of AMD can be reduced by consuming diets with high levels of lutein and zeaxanthin and supplementation by increasing their concentration in serum and parallel increase in macular pigment optical density (MPOD) [54,55,56,57,58].…”
Section: Lutein and Zeaxanthin Carotenoidsmentioning
confidence: 99%